Breast cancer risk factors and the mammarian nodule detection – opinion of mastectomized women - Melo, Elizabeth Mesquita; Silva, Raimunda Magalhães da; Rodrigues, Dafne Paiva (Rev Rene, 2000)
In this study the knowledge of the mastectomized women is approached concerning the contributing factors to their disease and treatment. It was aimed the breast cancer risk factors identification by the mastectomized women. This is an exploratory and descriptive research developed at a mastology clinic of a public institution with 12 women. The data were obtained through a semi-structured interview and, soon after, organized in tables. In the analysis it was taken as reference the quantitative data which were complemented by some important participant’s speeches. It was noticed that these didn’t associate work, feeding or oral contraceptive use to the disease, but the hereditariness and addictions. The path for the treatment was expressed in a satisfactory way, because in the big majority of times the mammarian surgery was accomplished in a short period of time, that varied from one to three months in relation to the cancer’s discovery. We concluded that the women’s knowledge about the related mammal’s cancer factors is restricted and, they don’t notice their influence in the appearance of the disease.